Hubungan Senam Hamil terhadap Lama Persalinan Kala II pada Wanita Primigravida di RSKIA Sadewa Yogyakarta - Yazidah, lzzatul; Hasibuan, Saribin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Maternal Mortality Rate (MMR) is one indicator to see the health status of women. Figures mortality mother is a/so one of the set targets in the millenium development goals to 5 of improving maternal health in which the targets to be achieved until the year 2015 is reduced to % the maternal mortality risk. Many factors cause the high MMR. One is the emotional state of pregnancy until the birth of a baby. During pregnancy, women experience physical and physico/ogical changes that occur due to hormonal changes. This change will simplify the fetus to grow and develop until birth. Pregnant womenin desperate need of fitness and optimal health to avoid risks that could jeopardize his condition and the fetus. Condition fit and healthy will help the mother in carrying out routine daily activity is recommended during this period is pregnancyexercise. The author would like to give an idea of the knowledge and benefits of pregnancy exercise of primigravida women in order to facilitate the birth process. The study was a cross sectional study. The subjects were primigravida women who give birth and do gymnastics in RSKIA Sadcwa pregnant by 60 people. Data analysis by using Chi Square test with significance level p = 0,05. Chi Square test was used to test whether there is any relationship between pregnancy exercise on the long second stage of labor in primigravida women in RSKIA Sadewa. From the results of Chi Square test showed p = 0,001. rherefore p < 0,05. The H1 was accepted. This means that the hypothesis in the study stated that there is a relationship between pregnancy exercise on the long second stage of labor in primigravida women. These result indicCJte that pregnant women who exercise will have second stage of labor is higher than pregnant women who did not exercise. Pregnancy exercise is good exercise for the mother before delivery. Statistical analysis showed p value < 0,05 is 0,001 then this proves that there is a relationship between pregnancy and old gymnastic second stage of labor in primigravida women.